WORM'S-EYE VIEW ON ‘AGRICLINICS AND AGRIBUSINESS CENTRES SCHEME’ (ACABC) OVER A DECADE IN CONTEXT TO MADHYA PRADESH, INDIA - Deepak Pal; Laveena Sharma, (International Journal on Recent Trends in Business and Tourism (IJRTBT), 2021)
Six decades ago, Mahatma Gandhi observed, "Agriculture is the backbone of the Indian economy." The scenario is still the same now, with agriculture, which is the mainstay of the communities, supporting practically the whole economy. It accounts for around 52 per cent of the Indian population's employment and generates 16 per cent of the country's overall GDP. The rapid growth of agriculture is necessary not just for self-sufficiency but also to earn crucial foreign exchange. Despite the fact that millions of farmers are marginal and small, Indian farmers are unrivalled in terms of production and productivity. They are just as quick to accept improved agricultural technologies as farmers in rich countries. It is believed that by providing timely and enough inputs such as fertilisers, seeds, and pesticides, as well as making reasonable agricultural loans and crop insurance available, Indian farmers will secure the nation's food and nutritional security. As a result, on April 9, 2002, the ‘Agri-Clinics and Agri-Business Centres' plan was created to increase technology transfer and extension services, as well as provide self-employment opportunities to technically skilled people. Herein after, we imagined the state of Madhya Pradesh from a worm's-eye perspective, which is a view of a scheme from below, as if the observer were a worm; it can be used to make an object appear big, strong, and mighty while the viewer feels childish or helpless. So, we here go through the actual facts by covering about the scheme, NTIs, trained candidates &venture established.